Teachers', Board Members' and Citizens' Perceptions of Educational Issues: A Comparative Study - John W. Skehan; James F. Doughty (Journal of Research in Rural Education, 1983)
This paper presents a comparison of the attitudes held by elected school officials, teachers and community members concerning eighteen current educational issues. The study is an outgrowth of community attitude surveys conducted in fifteen Maine communities by the Center for Educational Field Services, College of Education, University of Maine at Orono.